Integral Control of Health Hazards in Hospital Environment. Issue 5 (October 2013) - Dovjak, Mateja; Kukec, Andreja; Kristl, Živa; Košir, Mitja; Bilban, Marjan; Shukuya, Masanori; Krainer, Aleš
Hospitals present complex indoor environment with various users, health hazards and specific activities. This paper classifies health hazards specific to the hospital environment (HE), defines their interactions and possible impacts on human health and summarizes recommendations for biological and chemical hazards. A detailed literature review clearly shows that there is no developed system or method for integral control of health hazards in HE. There is no appropriate technology available that would allow development of optimal thermal comfort conditions for individual users in HE. For integral control of physical hazards, an innovative low exergy (LowEx) system was designed and tested. The system enables individual control of thermal comfort parameters to meet the needs of various users in the same room. It enables the design of optional conditions for healthcare and treatment considering the different requirements of individual patients and thermally neutral zones for other users. The system application is presented in a model room for burns patient. The measured energy use was lower by 11–27% for space heating and by 32–73% for cooling, when using LowEx system as compared to the conventional system. Owning to its flexibility, the system can also be used for other potential users.